The Impact of Medication Adherence and Depression on Stroke Recurrence in Post-Stroke Patients at Taman Husada Regional General Hospital - Fauzi, Lailla Affianti; Wara Kushartanti; Novita Intan Arovah; Fauzi; Regina Maria; Adliah Anwar6; Decyta Khairun Nisa (Window of Health : Jurnal Kesehatan, 2025)
Patient compliance in adhering to stroke treatment recommendations becomes one of the factors influencing the occurrence of recurrent strokes. Depression in post-stroke patients inhibits functional brain recovery, increases the potential for recurrent strokes, lowers the quality of life, and raises the risk of death compared to patients without depression. The aim of this study is to analyze the relationship between drug therapy compliance and the level of depression on the occurrence of recurrent strokes in post-stroke patients. This cross-sectional study involved 60 patients aged between 30 and 85 years, all undergoing outpatient stroke treatment at a hospital in Indonesia. Recurrent stroke incidents were defined as experiencing a secondary stroke within 30 days after the initial stroke occurrence. Out of the total participants, 12 individuals had experienced recurrent strokes after their initial episode, while 48 patients had not experienced recurrent strokes up to the point of data collection. Medication adherence data were evaluated using the MMAS-8 (Morisky Medication Adherence Scale), and depression levels were measured using the PHQ-9 (Patient Health Questionnaire-9). The research results show that in the post-stroke patient group, the level of patient adherence is high at 41.7%, and in the recurrent stroke group, the level of patient adherence is moderate at 41.7%. Meanwhile, in the post-stroke patient group, the dominant depression level is low (50%), while in the recurrent stroke group, the dominant depression level is mild, followed by severe depression. The analysis indicates that medication adherence is not associated with stroke recurrence, while depression is related to stroke recurrence with an OR value of 2.060, p <0.05. Further research on more efficient monitoring methods and proper depression management is recommended to reduce the risk of stroke recurrence.